2013
DOI: 10.1007/s00011-013-0599-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of inflammatory cells and cytokines by peptide epitopes in vitro: a simple in-vitro screening assay for prioritizing them for in-vivo studies

Abstract: ApoB and HSP60 peptides induced T-cell proliferation and expansion of regulatory T cells with interleukin-10 and transforming growth factor-β secretion. In comparison, peptide A was a poor stimulator of T cells and was found to induce tumor necrosis factor-α secretion by activated T cells. ApoB and HSP60 peptides were found to reduce early atherosclerotic lesion formation in mice by 32.1 and 33.5 %, respectively, while the reduction with peptide A was 5.7 %. Thus the in-vitro assay shows an apparent correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Again, the same human ApoB (688-707) and hHSP60 peptide (153-163) were used with the aim to develop an in vitro assay to screen peptide molecules for their inflammatory properties. The results were similar to earlier studies using these peptides, with induced T cell proliferation and expansion of regulatory T cells with IL-10 and TGF-β secretion and reduction of early atherosclerotic lesion formation in mice by 32.1 and 33.5 %, respectively (Mundkur et al 2013b). It has recently been shown that resident commensal bacterial GroEL, but not mouse-derived HSP60, could cause naïve T cells to differentiate into CD4…”
Section: Hsp60 Tolerization In Atherosclerosissupporting
confidence: 91%
“…Again, the same human ApoB (688-707) and hHSP60 peptide (153-163) were used with the aim to develop an in vitro assay to screen peptide molecules for their inflammatory properties. The results were similar to earlier studies using these peptides, with induced T cell proliferation and expansion of regulatory T cells with IL-10 and TGF-β secretion and reduction of early atherosclerotic lesion formation in mice by 32.1 and 33.5 %, respectively (Mundkur et al 2013b). It has recently been shown that resident commensal bacterial GroEL, but not mouse-derived HSP60, could cause naïve T cells to differentiate into CD4…”
Section: Hsp60 Tolerization In Atherosclerosissupporting
confidence: 91%
“…When a combination of human apolipoprotein B (ApoB 688-707 ) and human HSP60 153-163 (hHSP60) peptide was used to immunize mice, an additive effect on atherosclerosis was found compared to single immunization [37] ; similar findings were reported by another study by the same group [38] . These peptides have also been successfully used orally with the aim of preventing progression of atherosclerosis [39,40] . Again, all these studies have only been performed on young animals and mbHSP65 tolerization has so far never been studied in chronic atherosclerosis of aged animals.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of atherosclerosis prevention was assessed for peptides derived from apolipoprotein B100 (ApoB), heat shock protein 60 (HSP60), and complement cascade (peptide A). Both ApoB and HSP60 appeared to reduce early atherosclerotic lesions in mice by 32.1 and 33.5%, respectively, while the reduction with peptide A was 5.7% [ 58 ].…”
Section: Vaccinationmentioning
confidence: 99%